Review of Cherniavska V. Olena, Yurko S. Tetyana (2018). Mechanism of Financial Support of Small Business: Foreign Experience and Domestic Practice.Poltava: PUET. – In Ukrainian - Olga Prokopenko (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
-